Effect of Landscape Changes on the Water Quality of Murchison Bay - Sridhar, Balaji Bhaskar Maruthi; Gidudu, Anthony (International Journal of Advanced Remote Sensing and GIS, 2020)
The water quality in Murchison Bay of Lake Victoria, the Africa’s largest fresh water lake, is on decline due to rapid urban sprawl, decrease in vegetative surface and increase in impervious surface of the drainage area resulting in eutrophication of the lake. The objectives of our study are 1) to analyze the nutrient and metal concentrations in the Murchison Bay; 2) to identify and map the long-term landscape changes in Murchison Bay Watershed (MBW); 3) to analyze the impact of the landscape changes on the water quality of Murchison Bay. Water samples were collected from Miami Beach (MB), Ggaba Beach (GB) and Mulungo Beach (MuB), along the Murchison Bay and analyzed for various metal and nutrient concentrations. Landsat satellite imagery, sampled over three decades (1995-2019) of the MBW were analyzed for the land cover changes. The chemical analysis of the water samples showed that the P concentrations were above the critical limits while the As and Pb concentrations were higher but remained below the critical limits in water. The remote sensing analysis reveal that the impervious surface in the MBW increased by about 21.9% while the vegetative surface decreased by 4.2% during the period of 1995 to 2019. The Chlorophyll a concentration in the Murchison Bay increased over the period of time resulting in deterioration of water quality. Integration of environmental chemical analysis along with geospatial data aids in understanding the impact of land scape changes on the Murchison Bay water quality and to identify the areas vulnerable to change.
Keywords: Urban Watershed; Lake Victoria; Wetlands; Remote Sensing; Landsat and Geographic Information Systems (GIS)